The snapper and grouper fisheries of the Abrolhos Bank, East Brazil shelf: fleet patterns, exploitation status and risk assessment - Previero, Marília (2018)
The fishery is a complex and dynamic socio-ecological system involving several actors and knowledge areas. Along the Brazilian coast the small-scale fisheries are very common and provide important ecosystem services. This fishery modality are usually data-poor in terms of catch and abundance data, landing records, quantification of vessels and fishing gear used. This data-limited condition frequently hampers fishery assessments and effective managements. That is the case in the Abrolhos Bank, East Brazil, a wide portion of the shallow continental shelf that encompass a complex benthic habitat with coral reefs, rhodoliths, buracas, mangroves, seaweed banks and with a great biodiversity. Over this area the small-scale fisheries are a traditional activity, extremely diverse in terms of exploitation capacity, fishing gears, target stocks and operating areas. On the Abrolhos Bank, snappers and groupers are very common resources, besides being predators important for the ecosystem equilibrium. However, these stocks are not evaluated or continuously monitored in the fishing landings and any regional fishery management is currently in place. The overall goal of this thesis was to elucidate questions on three snappers (Lutjanus jocu, Lutjanus synagris and Ocyurus chrysurus) and three groupers (Cephalopholis fulva, Epinephelus morio and Mycteroperca bonaci) fishery characteristics, impacts and sustainability in the Abrolhos Bank. The specific objectives were (1) to assess, organize, and analyze these fisheries to find out patterns on stocks occurrence, on fishing fleets and fishing areas, and to propose management units; (2) to examine the abundance trends and the exploitation status of the six stocks through indicators of size, biomass landed, mortality, spawning and yield, and (3) to evaluate the stocks risk to overexploitation and their fishery sustainability considering biological, environmental social and economic aspects. The study was conducted in four coastal communities of the Abrolhos Bank. The data were obtained by interviews with fishers, experts and stakeholders, from fishery landings monitoring databases, by specimens\' measures in landings and from literature. Groups of stocks co-occurring in landings and groups of stocks co-occurring in fishing grounds were discovered. Seven similar fishing areas were determined and suggested as spatial management units. Overfishing and decline in the relative abundance were detected to five stocks. The major causes of overfishing were high fishing mortality, low spawning potential ratio, low mega-spawners and high juveniles in landings. The fishery has led some stocks on alert to overexploitation and the results revealed that coral reefs habitat and ecosystem are also threaten by mining waste and dredging. Furthermore, there is a weak environmental governance in the region and insufficient community participation in the construction of management proposals. The results reveal a concerning situation regarding the stocks exploitation status but provide the key points to be worked on together the fishing communities. This thesis emphasizes the need for urgent elaboration of fishery regulation measures in the region and may contribute in the delineating of management proposals in this complex and threatened fishery system.